El sentido moderno de la reforma universitaria en la obra filosófica de Eli de Gortari - Álvarez Cabrera, Jaime (Universidad Michoacana de San Nicolás de Hidalgo, 2009)
Eli of Gortari is a Marxist intellectual that played him/her to live in Mexico, in the times of the Second world Guerra and Guerra Fries, pupil of big intellectuals as Carlos Pellicer and Lombard Vicente Toledano, in their philosophical work is a proposal of Reformation University student. Its position regarding the university Reformation is divided in two stages: The first stage corresponds to the decades of the fifty and sixty that is characterized to defend the University of State (he believed that it was about a revolutionary state), in their concept, the University it lacks Autonomy and of Freedom of Class and of Investigation; in spite of that, gives an unusual priority to the Scientific Investigation and a strong one it disciplines Docencia, what could take to the practice being a rector of our Maxim House of Studies of 1961 to 1963. And the second stage corresponds to the decade of the eighty, when it already accepts that the University enjoyment of Autonomy and of Freedom of Class and of Investigation; it continues him/her giving priority to the Scientific Investigation and you it worries for that the investigators have material better conditions of work and a bigger participation in government's organs university student. But their biggest concern is that there is Internal democracy in the universities; but don't unite democracy of massive participation and direct, but rather it proposes a representative and indirect democracy, maybe as aftertastes of the "democratic Soviet centralism."

Eli de Gortari es un intelectual marxista, que le tocó vivir en México, en los tiempos de la Segunda Guerra mundial y la Guerra Fría, discípulo de grandes intelectuales como Carlos Pellicer y Vicente Lombardo Toledano, en su obra filosófica se encuentra una propuesta de Reforma Universitaria. Su posición respecto a la Reforma universitaria se encuentra dividida en dos etapas: La primer etapa corresponde a las décadas de los cincuenta y sesenta, que se caracteriza por defender la Universidad de Estado (él creía que se trataba de un estado revolucionario), en su concepto, la Universidad carece de Autonomía y de Libertad de Cátedra y de Investigación; a pesar de eso, le da una inusual prioridad a la Investigación Científica y una férrea disciplina a la Docencia, lo que pudo llevar a la práctica siendo rector de nuestra Máxima Casa de Estudios de 1961 a 1963. Y la segunda etapa corresponde a la década de los ochenta, cuando ya acepta que la Universidad goce de Autonomía y de Libertad de Cátedra y de Investigación; le sigue dando prioridad a la Investigación Científica y se preocupa por que los investigadores tengan mejores condiciones materiales de trabajo y una mayor participación en los órganos de gobierno universitario. Pero su mayor preocupación es que haya democracia Interna en las universidades; pero no una democracia de participación masiva y directa, sino que propone una democracia representativa e indirecta, quizás como resabios del “centralismo democrático” soviético.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Programa Institucional de Maestría en Filosofía de la Cultura
Keywords: info:eu-repo/classification/cti/4; IIF-M-2009-0024; Político; Ideología; Obra; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/55